Dissecting the Role of NF-κb Protein Family and Its Regulators in Rheumatoid Arthritis Using Weighted Gene Co-Expression Network - Sabir, Jamal S. M.; El Omri, Abdelfatteh; Banaganapalli, Babajan; Al-Shaeri, Majed A.; Alkenani, Naser A.; Sabir, Mumdooh J.; Hajrah, Nahid H.; Zrelli, Houda; Ciesla, Lukasz; Nasser, Khalidah K.; Elango, Ramu; Shaik, Noor Ahmad; et al. (Frontiers in Genetics, 2019)
Rheumatoid arthritis (RA) is a chronic synovial auto-inflammatory disease that destructs the cartilage and bone, leading to disability. The functional regulation of major immunity related pathways like NF-kB which is involved in the chronic inflammatory reactions underlying the development of RA remains to be explored. Therefore, this study has adopted statistical and knowledge based systemic investigations (like gene correlation, semantic similarity and topological parameters based on graph theory) to study the gene expression status of NF-kB protein family (NKPF) and its regulators in synovial tissues to trace the molecular pathways through which these regulators contributes to RA. A complex Protein-Protein Interaction Map (PPIM) of 2742 genes and 37032 interactions was constructed from differentially expressed significant genes (p value ≤ 0.05). PPIM was further decomposed into a Regulator Allied Protein Interaction Network, RAPIN, based on the interaction between genes (5 NKPF, 31 seed, 131 hubs and 652 bottleneck). Pathway network analysis has shown the RA specific disturbances in the functional connectivity between seed genes (RIPK1, ATG7, TLR4, TNFRSF1A, KPNA1, CFLAR, SNW1, FOSB, PARVA, CX3CL1 and TRPC6) and NKPF members (RELA, RELB, NFKB2 and REL). Interestingly, these genes are known for their involvement in inflammation and immune systems (signaling by Interleukins, Cytokine Signaling in Immune system, NOD-like receptor signaling, MAPK signaling, Toll-like receptor signaling and TNF signaling) pathways connected to RA. This study for the first-time reports that SNW1 along with other NK regulatory genes plays an important role in RA pathogenesis and might act as potential biomarker for RA. Additionally the proposed genes might play important roles in RA pathogenesis, as well as facilitate the development of effective targeted therapies. Our integrative data analysis and network-based methods could accelerate the identification of novel drug targets for RA from high throughput genomic data.